2010
DOI: 10.1007/s11666-010-9579-8
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Tribological Characteristics of HVOF Coatings Sprayed from Powder Blends of Cr3C2-25NiCr and NiCrBSi Alloy

Abstract: HVOF spraying was used to prepare coatings from mechanical blends of Cr 3 C 2 -25NiCr and NiCrBSi powders. The aim of this study is to study the tribological behavior of coatings prepared from such powder blends. The coatings were studied under dry sliding conditions particularly at high temperatures. Tribological properties of the coatings were characterized using a specific hot-button tribological tester at the temperature of 300°C in air, and a pin-on-disk test at room temperature. Addition of NiCrBSi resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Among thermal spraying processes, high velocity oxy-fuel spraying (HVOFS) is one of the most advantageous, as it allows to obtain denser coatings with lower oxide content and higher adhesion [ 4 ]. For HVOFS MMC coatings, Ni-based self-fluxing alloys (NiCrSiB) were found to be an optimal choice as the matrix material [ 5 ]. In this case, tungsten carbide-cobalt hardmetals (WC-Co) are commonly used as reinforcement [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among thermal spraying processes, high velocity oxy-fuel spraying (HVOFS) is one of the most advantageous, as it allows to obtain denser coatings with lower oxide content and higher adhesion [ 4 ]. For HVOFS MMC coatings, Ni-based self-fluxing alloys (NiCrSiB) were found to be an optimal choice as the matrix material [ 5 ]. In this case, tungsten carbide-cobalt hardmetals (WC-Co) are commonly used as reinforcement [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the fundamental areas where traditional NiCrSiB coatings require improvement is in hardness as it falls inferior to materials like carbides and ceramics. However, literature [7][8][9][10][11] on NiCrSiB with various additives show improved erosion and corrosion resistance. In this aspect, additives reported having shown improvements in NiCrSiB are Tungsten carbide, Chromium carbide, Titanium carbide, Aluminium oxide, Titanium dioxide, Silicon carbide, Cerium oxide, and Zirconium dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of science and technology, the corrosion resistance and other performance requirements of materials are continuously improved [1]. In order to improve the wear resistance and corrosion resistance of materials, materials such as nickel, cobalt, titanium and tungsten-based alloys and ceramics are usually used as coating materials [2,3]. Many studies have also reported that nickel-based coatings improve the wear and corrosion resistance of the substrate [4,5], by means of physical, chemical and electrochemical deposition.…”
Section: Introductionmentioning
confidence: 99%